Hope for common ground : mediating the personal and the political in a divided church - Rubio, Julie Hanlon (Moral traditions series., 2016)
Much like American society, the American Catholic Church is sharply divided: conservatives see government as the problem while liberals see government intervention as necessary. From the high point of Catholic consensus in the early 1960s with the election of John F. Kennedy, today Catholics in this country are less united than at any point in their history. Not only do Catholics disagree on abortion, same-sex marriage, physician-assisted suicide, and social spending, but they also disagree about what the major social problems are. Despite these rancorous divisions, many Catholics share concerns about avoiding cooperation with evil and working within communities to solve social problems. Rubio tries to expand this existing common ground and argues, with a vision of what she calls faithful citizenship, that more can be done at the local level if those on the right and the left could come and reason together instead of remaining mired in tired debates over political v. personal morality. Rubio uses this framework of common ground to analyze four hot-button ethical and policy issues--the family, poverty, abortion, and end-of-life care--in the hope of initiating dialogue and inspiring communal action.